2004
DOI: 10.1002/jctb.1115
|View full text |Cite
|
Sign up to set email alerts
|

Transformation products of bisphenol A by a recombinant Trametes villosa laccase and their estrogenic activity

Abstract: A Trametes villosa laccase, produced as a recombinant protein in Aspergillus oryzae, was purified to an electrophoretically homogeneous state and employed in studies on the metabolism of bisphenol A. Structural analysis of the bisphenol A reaction products by the enzyme indicated that the dimer, trimer, tetramer, pentamer, and hexamer of bisphenol A with C-C and/or C-O bonds between phenol moieties, were formed as the result of successive oxidative-condensation. The reaction mixture also contained oligomers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 10 publications
3
39
0
Order By: Relevance
“…In order to establish a standard protocol, a reaction using free (non- immobilized) laccase in the presence of 1 mM of BPA in McIlvaine buffer (pH 5) has been carried out. As previously reported [25,27,28], the oxidative transformation of BPA in the presence of laccase leads to the production of different metabolites, which have been analyzed as presented below.…”
Section: Catalytic Activity Measurementmentioning
confidence: 99%
“…In order to establish a standard protocol, a reaction using free (non- immobilized) laccase in the presence of 1 mM of BPA in McIlvaine buffer (pH 5) has been carried out. As previously reported [25,27,28], the oxidative transformation of BPA in the presence of laccase leads to the production of different metabolites, which have been analyzed as presented below.…”
Section: Catalytic Activity Measurementmentioning
confidence: 99%
“…Likewise halophenols [178][179][180][181][182] bisphenol A, [183][184][185] various hormones and so-called endocrine disrupting compounds [186][187][188] or even TNT [189,190] have been reported. Non-phenolic compounds may be ‗inactivated' using the LMS or PMS strategy [36,[191][192][193][194][195][196][197][198].…”
Section: Phenol Detoxificationmentioning
confidence: 99%
“…Formation of 4-isopropenylphenol and 4-(2-hydroxypropan-2-yl)phenol from the degradation of BPA by other laccases or peroxidase has been reported in previous studies (Fukuda et al 2004;Huang and Weber 2005).…”
Section: Identification Of Transformation Productsmentioning
confidence: 86%
“…While 4-isopropenylphenol may be released from the degradation of the formed oligomers (Fukuda et al 2004;Uchida et al 2001), other authors have suggested that this compound may be formed in a separate biodegradation route although it may also participate in the parallel pathway of polymerization (Michizoe et al 2005). It should be noted that previous research has demonstrated that BPA products after laccase treatment lack estrogenic activity (Fukuda et al 2004;TorresDuarte et al 2012) and BPA polymerization turns into precipitates, which is favorable to reduce its environmental impact (Torres-Duarte et al 2012). In addition, with the technology presented in the current research, the discharge of BPA polymerization products in the effluent of the EMR is not expected, since they must be removed by the nanofiltration membrane.…”
Section: Identification Of Transformation Productsmentioning
confidence: 92%
See 1 more Smart Citation